Calculation of Kinetic Parameters of the Thermal Decomposition of Residual Waste of Coniferous Species: Cedrus Deodara - Dhaundiyal Alok; Hanon Muammel M. (Acta Technologica Agriculturae, 2018)
This paper deals with pyrolysis decomposition of Cedrus deodara leaves with the help of thermogravimetric analysis (TGA). Experiments are performed in the presence of inert atmosphere of nitrogen. Experiments are conducted at three different heating rates of 5 °C∙min-1, 10 °C∙min-1 and 15 °C∙min-1 within temperature range of 35 °C to 700 °C. Arrhenius parameters such as activation energy and frequency factor are estimated by Flynn Wall and Ozawa (FWO), Kissinger-Akahira-Sonuse (KAS) and Kissinger. The activation energy and frequency factor calculated by using Kissinger method are 67.63 kJ∙mol-1 and 15.06 . 104 min-1 respectively; whereas the averaged values of the same parameters through FWO and KAS methods are 89.59 kJ∙mol-1 and 84.748 kJ∙mol-1, 17.27 . 108 min-1 and 62.13 . 107 min-1 respectively. Results obtained through Kissinger method represent the actual values of kinetic parameters. Conversely, FWO and KAS methods reflect the apparent values of kinetic parameters, as they are highly influenced by the overlapping of competitive reactions occur during pyrolysis.